2020
DOI: 10.7717/peerj.9486
|View full text |Cite
|
Sign up to set email alerts
|

Change of direction asymmetry across different age categories in youth soccer

Abstract: Background In youth, the development of change of direction (COD) and sprint performance is a key component for successfully competing in soccer across age. During a COD, the presence of directional asymmetries may be detrimental due to the unpredictable nature of the sport. Therefore, the aims of the study were to investigate asymmetries in COD ability and to examine the differences in COD and sprint performance across age in young soccer players. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
11
2
Order By: Relevance
“…This led to an increase in asymmetry as age rises ( Figure 1 ), which makes sense given the age-related performance changes, improving “good” but not “weak” CS. Unlike the current results, some authors concluded that asymmetry appears to emerge around periods associated with rapid growth (i.e., U16), possibly due to the demands of accumulated soccer-specific training and competitions, and the “motor awkwardness” phase that adolescents experience [ 22 ]. However, this study reported higher asymmetry values in older ages.…”
Section: Discussioncontrasting
confidence: 83%
“…This led to an increase in asymmetry as age rises ( Figure 1 ), which makes sense given the age-related performance changes, improving “good” but not “weak” CS. Unlike the current results, some authors concluded that asymmetry appears to emerge around periods associated with rapid growth (i.e., U16), possibly due to the demands of accumulated soccer-specific training and competitions, and the “motor awkwardness” phase that adolescents experience [ 22 ]. However, this study reported higher asymmetry values in older ages.…”
Section: Discussioncontrasting
confidence: 83%
“…Therefore, inter-leg differences regarding COD ability must be known to optimize soccer players’ preparation. In this sense, Trecroci et al 22 observed worse values in COD ability and CODD for the non-preferred leg in youth soccer players. These results were supported by Raya-González et al 8 in under-19 soccer players.…”
Section: Introductionmentioning
confidence: 93%
“…COD ability was tested over a 5 m + 5 m course with a turning point (90 • ) represented by a cone. For a better description of the test please refer to the work of Trecroci et al [22]. The distance between the starting line to the cone and between the cone to the finish line was 5 m each.…”
Section: Physical Performance Assessmentmentioning
confidence: 99%